MENYEMBUNYIKAN FILE TEKS PADA COVER AUDIO WAV DENGAN MENGGUNAKAN METODE LSB - Jonson Manurung (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2016)
Emerging technology makes a lot of changes in this world as well as with the increasing number of crime through computer access . Therefore, it needs an extra security to cover data privacy can only be accessed by certain circles . In the process of confidential data storage , companies still use a simple word processor in use. This research is to solve problems that occur in data security systems in the enterprise and also designing a new application that is user friendly so that it can better help protect data . Research carried out by way of analysis using the Unified Modeling Language ( UML ) financial section of AMIK Medicom , manufacture aplikasis steganography is to hide the text on the cover of an audio file wav . This study resulted in an application that can hide a text file with the information Corver Wav audio , the audio file size , bit rate , and audio length remains the same in accordance with the audio aslinya.file audio files using the Least Significant Bits ( LSB ) . Hopefully with this study can be generated that can be used as application system development to support and improve the performance of the company's operations